Effect of pores on the mechanical and durability properties on high strength recycled fine aggregate mortar - Rebeca Martínez-García; M.I. Sánchez de Rojas; P. Jagadesh; Fernando López-Gayarre; Julia M. Morán-del-Pozo; Andrés Juan-Valdes (Case Studies in Construction Materials, 2022)
Larger consumption of natural fine aggregates (NFA) leads to an increase in cost, energy, and negative environmental impact. On the contrary, the larger production of construction waste results in the generation of recycled fine aggregate (RFA), which requires safe disposal. The aim of study, is to the hunt for such alternatives, compares the mortar mechanical and durability properties with and without RFA. High strength mortar specimens were produced with mix proportion as 1:3 using RFA as partial replacement for NFA as 0%, 25%, 50% and 100%. The mechanical and durability performance of all specimens was assessed in the terms of compressive strength, flexural strength, water absorption and mercury intrusion porosimetry. Mechanical performance is confirmed by microscopic studies. The main results display that the mortar with 25% of RFA, performed better, which are related to pore structures and their distribution. It is noted that the, pores also increase with the increase in RFA content. The effect of pores on the strength and their relationships are assessed.